Interface design of environmentally friendly carbon nanotube-filled polyester composites: Fabrication, characterisation, functionality and application - C. S. Wu; H. T. Liao (eXPRESS Polymer Letters)
Polyhydroxyalkanoate (PHA) composites containing multi-walled carbon nanotubes (MWCNTs) were prepared using a process of melt-blending three-dimensional (3D) printing filaments. Maleic anhydride (MA)-grafted polyhydroxyalkanoate (PHA-g-MA) and chemically modified MWCNTs (MWCNTs-COOH) were used to improve the compatibility and dispersibility of the MWCNTs within the PHA matrix. Structural, morphological, thermal and mechanical characterisations revealed dramatic enhancements in the thermal and mechanical properties of the PHA-g-MA/MWCNTs-COOH composites compared with PHA, because of the formation of ester carbonyl groups through the reaction between MA groups of PHA-g-MA and the carboxylic acid groups of the MWCNTs-COOH. For example, with an addition of 1.0 wt% of MWCNTs-COOH, the initial decomposition temperature and tensile strength at failure increased by 72 °C and 16.0 MPa, respectively. Moreover, MWCNTs or MWCNTs-COOH enhanced the antibacterial activity and static dissipative properties of the composites. Composites of PHA-g-MA or PHA containing MWCNTs or MWCNTs-COOH had better antibacterial activities and antistatic properties.